QOLP-23. PHASE II RANDOMISED PLACEBO-CONTROLLED DOUBLE-BLIND STUDY OF ACETAZOLAMIDE VERSUS PLACEBO FOR CEREBRAL OEDEMA IN RECURRENT AND/OR PROGRESSIVE HIGH-GRADE GLIOMA REQUIRING TREATMENT WITH DEXAMETHASONE. (9th November 2020) - Agar, Meera; Nowak, Anna; Hovey, Elizabeth; Barnes, Elizabeth; Simes, John; Vardy, Janette; Wheeler, Helen; Leonard, Robyn; Hall, Merryn; Tim, Evonne; Spyridopoulos, Desma; Sim, Hao-Wen; et al.
Abstract: INTRODUCTION: Symptoms of raised intracranial pressure (ICP) in recurrent or progressive high-grade glioma (HGG) generally require corticosteroid treatment, often causing toxicity with variable effects on reversing ICP symptoms. Acetazolamide reduces ICP in other clinical settings including case series in glioma. AIM: To explore whether addition of oral acetazolamide enables safe dexamethasone dose reduction in management of raised ICP in recurrent and/or progressive HGG. METHODS: Participants had recurrent, progressive and/or persistent residual HGG requiring recommencement of dexamethasone, dose increase or dexamethasone dependency; prior/current bevacizumab was an exclusion. Eligible participants were randomised 1:1 to acetazolamide 250mg twice daily or placebo for 8 weeks. Standardised protocols were used for dexamethasone dose changes in both arms, with planned dose decrease from day 5 once ICP symptoms were stable. The primary endpoint was a composite of dexamethasone dose reduction and stability of performance status. Secondary endpoints included toxicity and feasibility (accrual and compliance). RESULTS: Thirty participants of a planned sample of 84 were enrolled (mean age 58 y (32-89)) from 7 Australian sites. The mean baseline dexamethasone dose was 6.2mg (4-16mg). Mean duration on treatment was 38 days (4-57) in placebo group and 31 days (3-60) in acetazolamide group, with 9 participants (30%) completing all study treatment (6 placebo, 3 acetazolamide). Study withdrawal was due to adverse events (n=6 (1 placebo, 5 acetazolamide)) and disease progression (n=6 (3 per arm)). Four participants (13%) (2 per arm) were stable responders meeting the primary endpoint criteria (≥50% corticosteroid dose reduction from baseline by 28 days maintained for 7 days, and no deterioration in performance status). Ten participants experienced a total of 13 serious adverse events (acetazolamide arm: 5 participants (33%), 6 events, 2 related). DISCUSSION: The addition of acetazolamide did not facilitate dexamethasone reduction. The study closed early due to poor accrual and increasing availability of bevacizumab.